Project-Based Short Video Creation For Instagram Reels: Enhancing Multimodal English Production Among Efl Learners - Lutfiana Lutfiana (Journal of World Science, 2026)
This study explores the impact of project-based short video making for Instagram Reels on the multimodal English production of EFL learners. Using a qualitative multiple case study approach, the research investigates learners’ collaborative processes, multimodal decision-making, and digital identity development. The findings show that integrating short-form digital storytelling in a project-based learning framework offers opportunities for authentic language use, creative expression, and multimodal composition. The project required active use of English, especially during scripting, rehearsing, and filming. Learners crafted messages for real or imagined audiences, improving fluency, confidence, and pragmatic awareness. They also enhanced their understanding of multimodal communication, combining verbal, visual, auditory, and gestural resources to convey meaning. Effective communication was seen as dependent not just on linguistic accuracy but on the orchestration of various semiotic modes. Additionally, the project fostered a sense of digital authorship, motivating learners to engage in modern online communication practices. This shift in identity increased motivation, engagement, and ownership, demonstrating the potential of social media–based learning tasks. The study highlights the effectiveness of Instagram Reels as an instructional tool in EFL classrooms, connecting language learning with digital practices while enhancing multimodal and digital literacies. Despite its limited scope, the study emphasizes the value of incorporating authentic, creativity-driven tasks into language education.